The impact of social health on global cognition and cognitive domains: An individual participant level data meta‐analysis of longitudinal cohort studies of cognitive ageing. (20th December 2022) - Samtani, Suraj; Mahalingam, Saly; Lam, Ben C. P.; Lipnicki, Darren M.; Costa, Erico; Xiao, Shifu; Guerchet, Maëlenn; Preux, Pierre‐Marie; Skoog, Ingmar; Scarmeas, Nikolaos; Kim, Ki Woong; Riedel‐Heller, Steffi G.; et al.
Abstract: Background: The Social Health and Reserve in the Dementia patient journey (SHARED) project is an international collaboration investigating the association between social health and cognitive function. We conducted an individual participant‐level meta‐analysis of the associations between social health variables and cognitive function (global cognition, memory, language, and executive function). Method: We obtained individual participant level data (N = 38, 641, mean age = 70.5 years, 58.49% female) from 13 longitudinal cohort studies of ageing (12 studies from the COSMIC consortium and the English Longitudinal Study of Ageing). Linear mixed models examined the impact of social health factors, namely relationship status, cohabitation, interactions with friends/family, community group engagement, perceived social support, loneliness, and having a confidante, on global cognition and cognitive domains (memory, language, and executive function). Result: After controlling for age, sex, and education, we found significant associations between social health variables and slower cognitive decline over time (Mean follow up = 4.99 years, SD = 3.71 years). Compared to being single, being in a relationship was associated with slower decline in global cognition ( b = 0.0132, 95% CI: 0.0044, 0.0220), and language ( b = 0.0180, 95CI%: 0.0015, 0.0346). Living with others was associated with slower decline in global cognition ( b = 0.0089, 95% CI: 0.0039, 0.0139), and memory ( b = 0.0155, 95%CI: 0.0031, 0.0279). Compared to never interacting with friends/family, weekly interactions were associated with slower decline in global cognition ( b = 0.0178, 95% CI: 0.0021, 0.0335) and memory ( b = 0.0198, 95% CI: 0.0094, 0.0302). Other social variables (community group engagement, loneliness and having a confidante) were not associated with cognitive decline. Conclusion: Good social health (specifically, being in a relationship, living with others, and interactions with friends/family) was associated with slower cognitive decline. Further research is required to investigate the causal pathways from social health to cognitive health.